Riding an elephant: A qualitative study of nurses' moral journeys in the context of Medical Assistance in Dying (MAiD) - Pesut, Barbara (J Clin Nurs, 2020)
AIMS AND OBJECTIVES: To describes nurses' moral experiences with Medical Assistance in Dying in the Canadian context. BACKGROUND: Nurses perform important roles in Medical Assistance in Dying in Canada and do so within a unique context in which Medical Assistance in Dying is provided through healthcare services and where accessibility is an important principle. International literature indicates that participating in Medical Assistance in Dying can be deeply impactful for nurses and requires a high degree of moral sense‐making. DESIGN: A qualitative interview study guided by Interpretive Description using the COREQ checklist. RESULTS: Fifty‐nine nurses from across Canada participated in the study. The decision to participate in Medical Assistance in Dying was influenced by family and community, professional experience and nurses' proximity to the act of Medical Assistance in Dying. Nurses described a range of deep and sometimes conflicting emotional reactions provoked by Medical Assistance in Dying. Nurses used a number of moral waypoints to make sense of their decision including patient choice, control and certainty; an understanding that it was not about the nurse; a commitment to staying with patients through suffering; consideration of moral consistency; issues related to the afterlife; and the peace and gratitude demonstrated by patients and families. DISCUSSION: The depth of nurses' intuitional moral responses and their need to make sense of these responses are consistent with Haidt's theory of moral experience in which individuals use reasoning primarily to explain their moral intuition and in which moral change occurs primarily through compassionate social interaction. Further, work on the moral identity of nursing provides robust explanation of how nurses' moral decisions are contextually and relationally mediated and how they seek to guard patient vulnerability, even at their own emotional cost. CONCLUSION: Medical Assistance in Dying is impactful for nurses, and for some, it requires intensive and ongoing moral sense‐making. RELEVANCE TO CLINICAL PRACTICE: There is a need to provide support for nurses' moral deliberation and emotional well‐being in the context of Medical Assistance in Dying care.